Increased expression and cellular localization of spermine oxidase in ulcerative colitis and relationship to disease activity - Hong, Shih-Kuang S.; Chaturvedi, Rupesh; Piazuelo, Blanca M.; Coburn, Lori A.; Williams, Christopher S.; Delgado, Alberto G.; Casero, Robert A.; Schwartz, David A.; Wilson, Keith T. (Inflammatory bowel diseases, 2010)
Polyamines are important in cell growth and wound repair, but have also been implicated in inflammation-induced carcinogenesis. Polyamine metabolism includes back-conversion of spermine to spermidine by the enzyme spermine oxidase (SMO), which produces hydrogen peroxide that causes oxidative stress. In ulcerative colitis (UC), levels of spermine are decreased compared to spermidine. Therefore, we sought to determine if SMO is involved in UC.MethodsColon biopsies and clinical information from subjects undergoing colonoscopy for evaluation of UC or colorectal cancer screening were utilized from 16 normal controls and 53 UC cases. Histopathologic disease severity was graded and the Mayo Disease Activity Index (DAI) and endoscopy subscore assessed. SMO mRNA expression was measured in frozen biopsies by TaqMan-based real-time polymerase chain reaction (PCR). Formalin-fixed tissues were used for SMO immunohistochemistry.ResultsThere was a 3.1-fold upregulation of SMO mRNA levels in UC patients compared to controls (P = 0.044), and a 3.7-fold increase in involved left colon versus paired uninvolved right colon (P < 0.001). With worsening histologic injury in UC there was a progressive increase in SMO staining of mononuclear inflammatory cells. There was a similar increase in SMO staining with worsening endoscopic disease severity and strong correlation with the DAI (r = 0.653, P < 0.001). Inflammatory cell SMO staining was increased in involved left colon versus uninvolved right colon.ConclusionsSMO expression is upregulated in UC tissues, deriving from increased levels in mononuclear inflammatory cells. Dysregulated polyamine homeostasis may contribute to chronic UC by altering immune responses and increasing oxidative stress. (Inflamm Bowel Dis 2010)